The effects of assertive communication training on communication skills of adolescents with online game users - Boby Nurmagandi; Achir Yani S. Hamid; Ria Utami Panjaitan (Universitas Aisyah Pringsewu, 2022)
The behavior of playing online games has the risk of causing problems for adolescents' developmental age, which is social relationship problems to addiction. Good communication skills can facilitate adolescents in assertive interpersonal relationships to prevent adolescents from online game problems. This study aims to determine the effect of assertive communication training on the communication skills of adolescents who play online games. Methods: This study applied a quasi-experimental pre-post test with a control group. The research respondents were selected using stratified, proportional, and simple random sampling techniques. 76 adolescents comprised the respondents of this study, divided into two groups. The respondents’ inclusion criteria were adolescents aged 15–16 years old who had played online games for at least the last 12 months. Results: The communication skills of adolescents in the intervention group has increased after implementing assertive communication training (p less than 0.05), in contrast to this, the communication skills of adolescents in the control group has not increased after the implementation of assertive communication training (p more than 0.05). Conclusion: Assertive communication training can be used as therapy in nursing services to improve communication skills and protect adolescents from the risk of social relationship problems to addiction due to online gaming activities.